Combustion and fragmentation of droplets of fuel oil/water emulsions - Shlegel N. E. Nikita Evgenjevich; Islamova A. G. Anastasiya Gomilievna; Klimenko A. Andrey; Shulyaev S. A. Stanislav Antonovich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen